“I Just Feel Fully Alive”: Enhancing Ecological Understandings Through Place-Based Experiences - MacDonald, Jennifer (Journal of the Canadian Association for Curriculum Studies, 2025)
This paper delves into the phenomenon of being fully alive—aliveness—as a process for recognizing and attuning to holistic and ecological understandings. In the context of outdoor education, I narrate the experience of an initially reluctant hiker who expressed a profound sense of energy and connection during a backpacking trip. This story leads to a deeper inquiry into the meaning, ambivalence and potential of feeling fully alive for curriculum and pedagogy. I show how the sensation comes as and with mystery to offer counter-conventional insights rethinking paradigms of mastering skills and conquering nature. Then, I offer four pedagogical realizations to enhance ecological understandings through place-based experiences.